Desain Kontrol Multi – Input DC–DC Converter Sistem Hibrid Turbin Angin dan Sel Surya Menggunakan Kontrol Fuzzy Logic untuk Tegangan Rendah - Pamuji, Feby Agung; Dibyo, Soe (Jurusan Teknik Elektro Universitas Andalas, 2015)
this paper describes a hybrid system that consist of Wind Turbines and Photovoltaic to supply electricity continuously for load. Output of Wind Turbines and Photovoltaic is controlled in order to generate maximum power. Multiple-input dc-dc converters is used to control power flow in order to have MPP (Maximum Power Point). Converter control using Fuzzy logic controller to control the output in order to be obtained MPP (Maximum Power Point) from Wind Turbines and Photovoltaic, so the efficiency of wind turbines and photovoltaic can be improved.Keywords : Maximum Power Point, Hybrid System, Fuzzy logic controllerAbstrak—Dalam makalah ini diuraikan sistem hibrid yang menggabungkan Turbin Angin dan Photovoltaic untuk memasok listrik terus-menerus pada beban. Output dari Turbin Angin dan Photovoltaic diatur agar menghasilkan daya yang maksimum. Konverter multiple-input buck-boost dc-dc digunakan untuk mengatur aliran daya agar didapatkan MPP(Maximum Power Point). Kontrol konverter menggunakan Fuzzy Logic controller untuk mengkontrol output sehingga didapat MPP(Maximum Power Point) dari Turbin Angin dan Photovoltaic, sehingga effisiensi dari Turbin Angin dan Photovoltaic dapat ditingkatkan.Kata Kunci : Maximum Power Point, system hibrid, Fuzzy Logic controller